Electric charge in clouds at temperatures above 0° C (MAUSAM, 1959)
It is well-established that heavy rain can fall under certain conditions, from clouds whose temperatures are nowhere below the freezing point and where the Bergeron mechanism is pot applicable, and coalescence of droplets can provide the initial step in the growth of rain drops. It is, however, generally believed that lightning discharges occur in heavy cumulus or cumulonimbus clouds in which glaciations has begun to be apparent, and most of the theories so far advanced on the development of electric charges in the clouds assume the change of state to play a direct role in the electrification of the cloud.